Lucius Cornelius Sulla in der antiken Erinnerung Jener Mörder, der sich Felix nannte - Eckert, Alexandra (Millennium-Studien / Millennium Studies, 2016)
Lucius Cornelius Sulla led his army against Rome, devastated Athens, and, as dictator, took bloody revenge on his enemies after his victory in the Civil War. His iconoclasm was infused in the collective memory of Greeks and Romans for many generations. Based on the concepts of cultural trauma and cultural memory, this book presents the first comprehensive study on the ancient memory of Sulla, covering a period of almost 400 years.